1998
DOI: 10.1128/jb.180.16.4056-4067.1998
|View full text |Cite
|
Sign up to set email alerts
|

Branched-Chain Amino Acid Biosynthesis in Salmonella typhimurium : a Quantitative Analysis

Abstract: We report here the first quantitative study of the branched-chain amino acid biosynthetic pathway in Salmonella typhimurium LT2. The intracellular levels of the enzymes of the pathway and of the 2-keto acid intermediates were determined under various physiological conditions and used for estimation of several of the fluxes in the cells. The results led to a revision of previous ideas concerning the way in which multiple acetohydroxy acid synthase (AHAS) isozymes contribute to the fitness of enterobacteria. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(17 citation statements)
references
References 70 publications
1
15
0
Order By: Relevance
“…Because the accumulation of isoleucine and valine is so closely tied to the concentrations of so many other key metabolites, the cell may monitor its metabolic state by having a regulatory protein (CodY) that responds directly to isoleucine and valine concentrations. The intracellular concentrations of BCAAs in Escherichia coli and Salmonella have been reported to range from 8 mM to 15 mM (Epelbaum et al, 1998). This range is consistent with those used in our experiments for B. subtilis CodY.…”
Section: Discussionsupporting
confidence: 91%
“…Because the accumulation of isoleucine and valine is so closely tied to the concentrations of so many other key metabolites, the cell may monitor its metabolic state by having a regulatory protein (CodY) that responds directly to isoleucine and valine concentrations. The intracellular concentrations of BCAAs in Escherichia coli and Salmonella have been reported to range from 8 mM to 15 mM (Epelbaum et al, 1998). This range is consistent with those used in our experiments for B. subtilis CodY.…”
Section: Discussionsupporting
confidence: 91%
“…Escherichia coli , Salmonella typhimurium and other enterobacteria encode three or more isozymes of AHAS that differ in preference for 2‐KB as the second substrate, inhibition by the pathway end‐product valine, affinity for cofactors and sensitivity to inhibition by the many herbicides that have been developed whose target is AHAS. The expression of each isozyme is regulated in a different way [2–4] and each presumably has a slightly different metabolic role [3–6]. On the other hand, many other prokaryotes have only a single AHAS, with most being similar in sequence and properties to an enterobacterial AHAS isozyme III.…”
Section: Introductionmentioning
confidence: 99%
“…ALS catalyzes the second step in isoleucine and the first step in valine biosynthesis, the formation of ␣-acetolactate and ␣-aceto-␣-hydroxybutyrate (51). Studies of Salmonella typhimurium and Escherichia coli have suggested that both an imbalance among ␣-ketoacids and end product deficiency contributed to inhibitor efficacy (12,30). Since ␣-ketoacids and their derivative acyl-CoA molecules are quantitatively predominant in biosynthetic metabolism (30a) and since similar imbalances are found in inborn errors of human metabolism Article published online before print.…”
mentioning
confidence: 99%